SUPLEMENTASI TEPUNG DAUN KELOR (Moringa oleifera) TERHADAP PERTUMBUHAN DAN KELULUSHIDUPAN IKAN BANDENG (Chanos chanos) - Nurmiyati, Nurmiyati; Jasmanindar, Yudiana; Liufeto, Franchy Ch. (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2023)
Bandeng fish (Chanos chanos) is a type of fish cultivated in brackish water. So that, with production centers in Bipolo Village, Kupang Regency. Moringa leaves are a material that can be used as raw material for artificial feed because it has a fairly complete nutritional content. The aim was to determine the growth and survival of milkfish (C. chanos) fed from moringa leaf meal (M. oleifera). The research was carried out for 2 months, taking place in Bipolo Village, Sulamu District, Kupang Regency. The research method used a completely randomized design (CRD) consisting of 4 treatments and 3 replications so that 12 research units were tried: treatment A = feed without 0% moringa leaf powder formulation, B = feed with 2% moringa leaf powder formulation, C = feed with 4% moringa leaf powder formulation, D = feed with 8% moringa leaf powder formulation. The maintenance period lasts between 60 days and 15 days apart to obtain research data. Parameters observed were absolute weight growth, daily growth rate, absolute length growth and survival. The results showed that the artificial feeding of moringa leaf powder had no significant effect on absolute weight growth, daily growth rate and survival (P>0.05) meanwhile absolute length growth had a significant effect (P<0.05). The absolute length growth was in treatment D (8.05 cm) and the lowest in treatment A (6.06 cm).